Early Failure of a Novel Modular Dual Mobility Liner After Metal Release: Clinical Presentation and Detailed Retrieval Analysis - Allan K. Metz, MD; Michael A. Kurtz, PhD; Cameron R. Egan, MD; Steven M. Kurtz, PhD; Christopher E. Pelt, MD (Arthroplasty Today)
Cobalt chrome alloy (CoCrMo) corrosion and subsequent metal release has been described as a potential complication of total hip arthroplasty. Here, we present the case of a patient with a well-seated dual mobility (DM) implant revised after 10 months. Prior to revision, the patient experienced pain and stiffness. Following a negative infection workup, we measured elevated metal concentrations, hypothesized to originate from the CoCrMo DM liner. While corrosion has been extensively reported in other constructs, the CoCrMo liner described here includes a post and tabs, features added to reduce the risk of corrosion. Retrieval analysis demonstrated a severe chemically based corrosion attack on the liner. Continued caution and ongoing close monitoring of outcomes associated with the use of modular DM constructs is likely warranted.